Aceh Besar تطبيق لعبة "من أنا؟" بكتاب العربية بين يديك في تدريس الكلام بمعهد دار مريم بنت إبراهيم - Mahmud, Salami; Fithriani, Fithriani; Ramadhani, Cut Putri (لســـانـنــا (LISANUNA): Jurnal Ilmu Bahasa Arab dan Pembelajarannya, 2023)
Students at Dar Maryam Binti Ibrahim Aceh Besar Islamic Boarding School study a variety of subjects, including speaking Arabic. This subject aims to make students able to speak Arabic correctly and fluently. However, the reality is that female students face some problems in learning to speak. Among them is the lack of vocabulary mastered by female students. Some of them are unable to use the vocabulary in speaking, and some of them are afraid of making mistakes when speaking Arabic. The purpose of this study was to determine the effectiveness of the application of the game "man ana?" with the book al-arabiyyah baina yadaik to develop students' ability to speak and their response to this application. The method used by researchers in this study is the pre-experimental design experimental method. The population in this study were all 242 students at the Dar Maryam Binti Ibrahim Islamic Boarding School in Aceh Besar, while the research sample was class II (B) students, totaling 32 students. The instruments that the researchers used in this research are pre-test post-test and questionnaire. The result of the research is that the application of the game "man ana?" with the book al-arabiyyah baina yadaik to develop students' ability to speak proved to be effective based on the T-test greater than the T-table (2,45 <12,21 > 1,69. While the response of students to this learning is positive with an average value of 96.42%.